Determination of Kerr and two-photon absorption coefficients of ABI thin films - Bundulis, Arturs; Nitiss, Edgars; Rutkis, Martins (SPIE, 2018)
In this paper we report the results of studied nonlinear optical properties of DMABI-Ph6 in form of solutions with chloroform as solvent and guest-host thin films with poly(methyl methacrylate) as host material. We implemented the Zscan method for studies of Kerr and two-photon absorption of selected material. During experimental measurements we used 1064 nm Nd:YAG laser with 30 ps pulse duration and 10 Hz repetition rate. From acquired values of Kerr coefficients we calculated values for real part of third-order susceptibility, as well as second-order hyperpolarizability. Acquired data for DMABI-Ph6 were compared with data for other ABI derivatives studied previously to describe how different donor and acceptor groups influence third-order nonlinear optical properties.
This material is based upon work supported by the ERDF 1.1.1.1 activity project Nr. 1.1.1.1/16/A/046 “Application assessment of novel organic materials by prototyping of photonic devices”
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Kerr effect; Nonlinear optics; Organic materials; Thin films; Two-photon absorption; Z-scan